Production Performance of Four Pig Herds Infected With Porcine Reproductive and Respiratory Syndrome Using the “Load-Close-Exposure” Approach in China - Zhang, Zhendong; Qu, Xiangyang; Wang, Xiaoquan; Li, Zhi; Yang, Shuqing; Sun, Liumei; Zhou, Bin (Frontiers in Veterinary Science, 2022)
Porcine reproductive and respiratory syndrome (PRRS) is one of the most important swine diseases, leading to enormous losses to the pig producers all over the world. The intervention measure of “load-close-exposure” (interrupting introduction of replacement pigs combined with whole-herd exposure to live PRRSV) has been widely used in North America and showed wonderful outcomes for controlling PRRS in the field. In the present study, we performed the analysis of the production performance after PRRS outbreak by adopting this measure for the first time in China. Our results showed that the development rate of gilts decreased by a mean of 8.56%, farrowing rate of breeding sows decreased from 86.18% to 77.61%, the number of piglets born alive per sow decreased by a mean of 0.73 pigs, and the pre-weaning and post-weaning mortality increased by a mean of 2.74% and 4.97% compared to the parameters of 6 months before outbreak. The time to PRRSV stability (TTS) defined as time in weeks it took to produce PRRSV negative pigs at weaning is an important indicator for controlling PRRSV successfully. The median TTS among herd A, C and D was 21.8 weeks (21.6 to 22.1 weeks), but the TTS for herd B was 42.3 weeks, which might be due to the twice introduction of gilts. Our quasi-experiment enriches data for controlling PRRS and implies that “load-close-exposure” strategy might be a good choice for Chinese producers and veterinaries.